A Systematic review on the prevalence and risk factors of depression among Chinese undergraduate students - Zhao, Mimi; Nor Ba'yah Abdul Kadir,; Muhammad Ajib Abd Razak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This review focuses on the prevalence of depression and its associated risk factors among Chinese undergraduates, particularly examining the impacts of the COVID-19 pandemic on their mental health. The aim is to deepen the understanding of depression's prevalence and risk factors within this group, providing a robust reference for future studies and interventions. A comprehensive search and review were conducted on 1,198 documents from CNKI, Web of Science, Scopus, and other relevant databases. The selection process involved deduplication, preliminary evaluation, and a thorough full-text review, culminating in 75 documents that adhered to rigorous analytical standards, including the detailed reporting of depression data, the use of standardized depression scale assessments, and focusing on ordinary Chinese undergraduates. The analysis identified 70 risk factors for depression, confirming that the prevalence of depression among these students is influenced by a complex interplay of sociodemographic, psychological, health status, and personal lifestyle factors. The review also highlights several methodological flaws in previous studies, such as simplified research methods and outdated references. The study underscores the need for future research to consider the impact of different cultural backgrounds on depression, to employ longitudinal studies to establish causal relationships, and to use theoretical frameworks to conduct more systematic and detailed analyses. These steps will enhance the understanding and development of effective interventions for improving the mental health of Chinese undergraduates in a post-pandemic context.